Sosialization of income tax article 21 to Bank Jateng Employees - Leny Mursitowati; Maruf, Muhammad Hasan; Suhesti Ningsih; Doni Budi Prasetyo (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
have into a real form of community service. Community Service Lecture (KKN) is also a concrete form of experience that includes education, research, and community service. The Community Service Activity of ITB AAS Indonesia was carried out at Bank Jateng, Sragen Branch Office. The purpose of this Community Service activity is to provide an understanding to Bank Jateng employees about the definition of Income Tax Article 21 (PPh21), income tax subjects, tax obligations, types of taxes, tax withholding rates, tax withholding flows and tax reporting. The method of community service activities is a qualitative method involving three stages including the observation method, interview method and counseling method. The target of the community service is the employees of Bank Jateng, Sragen Branch Office who are subjects of Income Tax Article 21 (PPh21). In conclusion, the community service activities carried out at Bank Jateng, Sragen Branch Office can provide positive results to employees regarding information on Income Tax Article 21 (PPh21). Kata kunci: Pajak Penghasilan Pasal 21 (PPh21), subjek pajak, jenis pajak,  tarif pajak, pelaporan pajak.